2020
DOI: 10.1186/s12889-020-08752-z
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of rural women with damages resulting from an earthquake in Iran: a qualitative study

Abstract: Background: Women, with more vulnerabilities and less access to resources, are often seen as victims of natural disasters. Therefore, the present study aimed to investigate the experiences of rural women with damages resulting from an earthquake in Iran. Methods: In this research, a qualitative approach, as well as the conventional content analysis was employed. The study population consisted of rural women residing in the earthquake-stricken areas of Sarpol-e Zahab and Salas-e Babajani counties in Kermanshah … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 45 publications
1
18
0
1
Order By: Relevance
“…People usually turn to religious rituals to achieve peace and quiet in times of calamity and other unexpected and terrifying situations [ 25 , 26 ]. The COVID-19 outbreak was unexpected, and no one knew when the pandemic would end or whether there would be any way to avoid or treat it.…”
Section: Resultsmentioning
confidence: 99%
“…People usually turn to religious rituals to achieve peace and quiet in times of calamity and other unexpected and terrifying situations [ 25 , 26 ]. The COVID-19 outbreak was unexpected, and no one knew when the pandemic would end or whether there would be any way to avoid or treat it.…”
Section: Resultsmentioning
confidence: 99%
“…Data saturation—a criterion to discontinue data collection or analysis until it has been observed that the point of no new themes or information has been reached [ 24 – 26 ]—is an important methodological principle in qualitative research. Collecting sample for this study was purposeful, and sampling criterion was the theoretical saturation [ 27 , 28 ]. This study concluded that the theoretical saturation point was reached after completing 22nd interview and there was no need to follow up with potential participants who did not respond to the invitation, based on the fact that no new themes or code was emerged.…”
Section: Methodsmentioning
confidence: 99%
“…The criterion for determining the number of samples was theoretical saturation which was obtained by interviewing 26 female-headed households in Kermanshah province. In qualitative research, theoretical saturation is when the continuation of the interviews no longer helps to generate new data and all codes are repeated so the researcher decides to stop the interview process [ 28 ]. In this study, all codes were repeated after interview 21, but the researchers continued the interview process for up to 26 people for more accuracy and confidence that they avoided false saturation.…”
Section: Methodsmentioning
confidence: 99%